10.1142/9789814343060 (CrossRef Listing of Deleted DOIs, 2000)
Panax notoginseng saponins (PNS), the chief saponin components of the traditional Chinese medicine Panax notoginseng, are known to ameliorate the outcomes of ischemic stroke (IS), primarily by mitigating inflammatory responses, enhancing microcirculation, and modulating oxidative stress. Damage to brain microvascular endothelial cells (BMECs) and BMECs' ferroptosis are critical steps in cerebral ischemia-reperfusion injury (CIRI), a process in which neutrophil extracellular traps (NETs) have been shown to induce BMECs injury, thereby aggravating CIRI. We aimed to investigate the regulatory effects of PNS on NETs and BMECs' ferroptosis following CIRI and evaluate its therapeutic efficacy in brain injury intervention. In this study, Sprague-Dawley rats were subjected to middle cerebral artery occlusion/reperfusion (MCAO/R), and the BMECs were exposed to oxygen-glucose deprivation/reoxygenation (OGD/R). These models were pretreated with PNS or the NETs-degrading agent DNase I, and the ensuing changes in key proteins, NETs-related markers, inflammatory factors, and ferroptosis-related indicators were assessed using Western Blotting or specific assay kits. Finally, neurological injury was assessed by neurological function scores and triphenyl tetrazolium chloride staining, while cell viability was evaluated using the Cell Counting Kit-8 (CCK-8) assay. In the rat models, PNS and DNase I markedly reduced the levels of key NETs biomarkers, related inflammatory factors, as well as MCAO/R-triggered ferroptosis, thereby mitigating brain injury. PNS treatment effectively suppressed NETs-induced ferroptosis in BMECs in vitro, thereby alleviating cell injury. This study demonstrated that PNS alleviates CIRI by inhibiting NETs and BMECs' ferroptosis. Mechanistically, PNS suppresses NETs, thereby suppressing ferroptosis. Collectively, these findings support a pharmacological rationale underlying the clinical treatment of IS.